A Semantic Literature Review on Crescent Visibility: Trends, Models, and Implications for the Islamic Calendar - Syarif, Muh Rasywan; Sakirman, Sakirman; Syarif, Muhammad Fazlurrahman (Fakultas Syari'ah dan Hukum UIN Walisongo, 2025)
The visibility of the hilāl is a fundamental aspect in determining the beginning of the Hijri month, which significantly impacts the implementation of worship and the social order of Muslims in various parts of the world. This study adopts a Semantic Literature Review approach to analyze research trends, prediction models, and the scientific and social implications of hilāl visibility in the Islamic calendar system. Various methods have been developed, ranging from classical astronomical models such as imkān ar-rukyat to the utilization of artificial intelligence and digital imaging technology. The results show that integrating astronomical methods with data-driven modeling and machine learning algorithms can improve the accuracy of hilāl visibility predictions. However, applying these models still faces challenges, especially regarding acceptance from Muslim communities and religious authorities. This study emphasizes the importance of collaboration between astronomical scientists and religious scholars in formulating a more accurate, inclusive, and globally acceptable Hijri calendar system.